Peculiarities of the musical language of the little suite "about the beasts" m. Stepanenko (Pedagogy of Higher and Secondary Education, 2009)
The author analyzes musical language of plays of a small suite «About animals», allocates of musical expressiveness used by the composer for a reconstruction of figurative dramatic art of musical text.
Keywords: composer; play; musical language; suite; figurativeness; means of musical expressiveness